Differential Expression of ADAM23, CDKN2A (P16), MMP14 and VIM Associated with Giant Cell Tumor of Bone - Conceição, André Luis Giacometti [UNESP]; Babeto, Erica [UNESP]; Candido, Natalia Maria [UNESP]; Franco, Fernanda Craveiro [UNESP]; Zuccari, Débora Aparecida Pires de Campos; Bonilha, Jane Lopes; Cordeiro, José Antônio; Calmon, Marilia Freitas [UNESP]; Rahal, Paula [UNESP] (Journal Of Cancer, 2015)
Though benign, giant cell tumor of bone (GCTB) can become aggressive and can exhibit a high mitotic rate, necrosis and rarely vascular invasion and metastasis. GCTB has unique histologic characteristics, a high rate of multinucleated cells, a variable and unpredictable growth potential and uncertain biological behavior. In this study, we sought to identify genes differentially expressed in GCTB, thus building a molecular profile of this tumor. We performed quantitative real-time polymerase chain reaction (qPCR), immunohistochemistry and analyses of methylation to identify genes that are putatively associated with GCTB. The expression of the ADAM23 and CDKN2A genes was decreased in GCTB samples compared to normal bone tissue, measured by qPCR. Additionally, a high hypermethylation frequency of the promoter regions of ADAM23 and CDKN2A in GCTB was observed. The expression of the MAP2K3, MMP14, TIMP2 and VIM genes was significantly higher in GCTB than in normal bone tissue, a fact that was confirmed by qPCR and immunohistochemistry. The set of genes identified here furthers our understanding of the molecular basis of GCTB.
Keywords: Giant cell tumor of bone; Gene expression; Hypermethylation; Immunohistochemistry